Effects of technology on knowledge, attitude and practice of pregnant women for childbirth - Ivna Silva Andrade; Régia Christina Moura Barbosa Castro; Karla de Abreu Peixoto Moreira; Cristina Poliana Rolim Saraiva dos Santos; Ana Fátima Carvalho Fernandes (Universidade Federal do Ceará, 2019)
Objective: to evaluate the effects of educational video on the knowledge, attitude and practice of pregnant women for active childbirth. Methods: a quasi-experimental study, developed in ten basic family health units, with 167 pregnant women in the last trimester, through a built and validated instrument to survey knowledge, attitude and practice. In the Intervention Group, the research was applied, accompanied by an educational session, with video exposure. For the Control Group, routine prenatal investigation and consultation were applied. Results: the Intervention Group presented greater adequacy in knowledge, attitude and practice, with significant statistics in all variables, highlighting the influence of educational video for active childbirth. Conclusion: the use of educational video stood out positively as educational technology for knowledge, attitude and practice of pregnant women in relation to active childbirth.